Design and simulation of electroacoustic sensor for exhaled breath analysis - Hazadi, Ahmad Hafiz Faqruddin; Md Ralib, Aliza Aini; Saidin, Norazlina (Institute of Electrical and Electronics Engineers Inc., 2018)
The development of medical study has led to the improvement of disease detection through breath analysis. The breath analysis is a study that analyze the volatile organic compounds (VOCs) in the human exhaled breath which can lead to the detection of diseases. Current technologies such as urine and blood test are invasive and painful. Hence, rapid detection of disease is proposed through breath analysis that is noninvasive. This work emphasizes on the establishment of electroacoustic sensor called quartz crystal microbalance (QCM) sensor. AT-cut quartz was chosen as the piezoelectric material and aluminum as the electrode. The QCM sensor is modelled and simulated using the COMSOL Multiphysics to evaluate the performances in term of resonance frequency, coupling coefficient and sensitivity. The simulated QCM sensor with quartz radius of 385 um resonates at 5.109MHz. The sensitivity of the sensor is 0.8449 MHz/ng after exposed to acetone gas which act as the breath marker for detection of diseases in exhaled breath.